A Reversible DNA Logic Gate Platform Operated by One‐ and Two‐Photon Excitations. Issue 1 (4th November 2015) - Tam, Dick Yan; Dai, Ziwen; Chan, Miu Shan; Liu, Ling Sum; Cheung, Man Ching; Bolze, Frederic; Tin, Chung; Lo, Pik Kwan
Abstract: We demonstrate the use of two different wavelength ranges of excitation light as inputs to remotely trigger the responses of the self‐assembled DNA devices (D‐OR). As an important feature of this device, the dependence of the readout fluorescent signals on the two external inputs, UV excitation for 1 min and/or near infrared irradiation (NIR) at 800 nm fs laser pulses, can mimic function of signal communication in OR logic gates. Their operations could be reset easily to its initial state. Furthermore, these DNA devices exhibit efficient cellular uptake, low cytotoxicity, and high bio‐stability in different cell lines. They are considered as the first example of a photo‐responsive DNA logic gate system, as well as a biocompatible, multi‐wavelength excited system in response to UV and NIR. This is an important step to explore the concept of photo‐responsive DNA‐based systems as versatile tools in DNA computing, display devices, optical communication, and biology. Abstract : Light logic : A four‐part, fluorophore‐modified DNA device is designed to operate as an OR logic gate in response to two excitation wavelengths. This device could be reset with excess oligonucleotides, and was shown to be taken up by cultured mammalian cells.